Optimization of Extraction Process of Isaria cicadae Miquel Spore Oil and Effect on Inflammation and Oxidative Damage of Intestinal Epithelial Cells - Xingyang LI; Beiqi WANG; Chao GUO; Hui CAO; Ruilian YU; Qin WANG (Shipin gongye ke-ji)
This study utilized solvent extraction to continuously reflux extract the lipid components of cultural Isaria cicadae Miquel spore powder, optimized the extraction process to maximize the yield of Isaria cicadae Miquel spores oil based on the single-factor experiments, and response surface analysis, explored its composition, anti-inflammatory activity in vitro and potential effects on repairing oxidative damage of intestinal epithelial cells. Results indicated that under the conditions of a liquid-solid ratio of 12:1 and a temperature of 55 ℃, the highest yield of Isaria cicadae Miquel spore oil was obtained after continuous countercurrent extraction for 3 hours, reaching 2.626%±0.04%. Additionally, 25 compounds were identified by gas chromatography-mass spectrometry (GC-MS) analysis, including 18 fatty acids, accounting for 87.86%. In vitro experiments demonstrated that Isaria cicadae Miquel spore oil at concentrations of 20~200 μg/mL, significantly increased RAW264.7 cell survival rate and significantly promoted cellular NO secretion to normal physiological levels under LPS-induced conditions (P<0.001). Moreover, at concentrations of 60~200 μg/mL, Isaria cicadae Miquel spore oil significantly promoted the proliferation of H2O2-induced Caco-2 cells (P<0.01), while concentrations of 40~100 μg/mL significantly enhanced the migration ability of Caco-2 cells (P<0.05). Thus, Isaria cicadae Miquel spore oil has the potential to promote the repair of oxidative damage to intestinal epithelial cells. As a component extracted from novel food materials, it holds promise for the development of foods for special medical purposes, targeting inflammatory bowel disease and intestinal mucosal injury.